Multiplicity one for certain paramodular forms of genus two - Rösner, Mirko; Weissauer, Rainer (L-functions and Automorphic Forms, 2017)
We show that certain paramodular cuspidal automorphic irreducible representations of GSp(4,AQ), which are not CAP, are globally generic. This implies a multiplicity one theorem for paramodular cuspidal automorphic representations. Our proof relies on a reasonable hypothesis concerning the non-vanishing of central values of automorphic L-series.